The Potential of Interpretation in the Geotourism Route in Khorat UNESCO Global Geopark : Sri Janasa Dvaravati Civilization Route, Sung Noen District, Nakhon Ratchasima Province - Lamwunnawong, Supaporn; Nualanan, Kamonthat; Pumisiripaiboon, Kwan-isara; Kowitwanitphan, Thanawat; Patthamaritthikul, Thanawat (Journal of Management Science Nakhonratchasima University, 2025)
This study aimed to investigate the current conditions and assess the potential of non-personal interpretation along the Khorat UNESCO Global Geopark tourism route: the “Dvaravati Sri Janasa Route” in Sung Noen District, Nakhon Ratchasima Province. The research employed both qualitative and quantitative methods, with data collected through observation, focus group discussions, and interpretation potential assessment forms. The sample group consisted of 45 participants, including representatives from geopark communities, temples, schools, academics, and relevant agencies. Data were analyzed using content analysis, and the potential was evaluated using mean scores categorized into five levels. The findings revealed that the existing non-personal interpretation media at many sites were in deteriorated condition, insufficient in quantity, and lacked visitor centers. Additionally, the number of site guides was inadequate. The potential assessment indicated that the site with the highest potential for non-personal interpretation was the Sung Noen Sandstone Historical Quarry (Ban Som Kob Ngam), which was rated as “excellent.” This was followed by the Sung Noen Railway Station Memorial and the Sandstone Reclining Buddha Image, which were rated as “very good,” respectively. Recommendations for enhancing interpretation potential included developing user-friendly interpretation materials suitable for training junior guides in the future, installing additional directional signage at road junctions near the sites, establishing a system that allows tourists to contact community leaders for guided visits, and organizing training sessions led by knowledgeable or well-known individuals to raise awareness among community members.